A new species of the genus Lejeunea Lib. (Marchantiophyta, Lejeuneaceae) from Brazil - Bastos, Cid José Passos; Reiner-Drehwald, María Elena; Schäfer-Verwimp, Alfons (Phytotaxa, 2017)
The new species Lejeunea flagellifera from Brazil is described and illustrated. This species is characterized by its large size, the large, inflated and rectangular leaf lobule and by flagelliform branches with caducous leaves. The specimens were found in montane ombrophilous forests, growing on bark and living leaves of trees.